Child Traumatic Stress and the Sacred: Neurobiologically Informed Interventions for Therapists and Parents - De Luna, Joseph E. (Religions, 2021)
Children experience trauma and adverse experiences at an alarming rate. The negative impact of traumatic experiences on a child’s developing brain is pervasive, adversely affecting one’s thoughts, feelings, behaviors, physiological reactions, and social relationships. Conversely, the nature, pattern, timing and duration of therapeutic experiences can change the brain in ways that support and cultivate therapeutic growth and healing. The purpose of this paper will be to review and expand on two prominent neurobiological therapeutic frameworks within the field of child trauma therapy: the Neurosequential Model of Therapeutics and Interpersonal Neurobiology. We will discuss the ways in which trauma experiences are organized in the brain and how therapeutic and parenting interventions can address the key areas of the brain that are impacted. Further, this paper will expand on these frameworks to explore how the sacred (within primarily a Judeo-Christian monotheistic religious tradition) can be integrated within the therapeutic process—specifically through the themes of safety, relational connection, and meaning-making.